PENILAIAN DIAGNOSTIK PADA MATA PELAJARAN FIQIH DI MADRASAH TSANAWIYAH NEGERI 1 PONTIANAK TAHUN PELAJARAN 2022/2023 - Rudiansyah Rudiansyah; Ali Hasmy; Sulaiman Sulaiman (IAIN Pontianak, 2023)
Numerous students have trouble comprehending concepts relating to Fiqh subject mater, which is why this study was carried out. These learning problems are also exacerbated by the lack of diagnostic testing. In addition, the research intends to describe the design, execution, processing, and reporting of diagnostic assessment results based on earlier diagnoses of the problem. This study approached a qualitative methodology with descriptive methods. The research participant involved 12 students, 1 instructor of Islamic studies, and 2 school administrators. The technique is in the from of document analysis, observation and direct conversation. Data analysis used study were data gathering, condensing, presenting, conclusion and verification. Utilizing member check, source triangulation, time triangulation and engineering triangulation are approaches for validating data. The results of this study are: 1) Diagnostic assessment planning The teacher sets the goals for the assessment, evaluates the material based on the syllabus and lesson plans, uses the previous grid to create the questions, and creates answer keys; be that as it may, do never again look at the inquiries.2) Implementation of the Diagnostic assessment, including setting up the classroom and explaining the rules that students must follow, such as not arriving late, not being honest, participating, sitting together, handing out answer sheets, working on them, and checking them. The learning outcomes of the students improved, learning difficulty was minimized and the learning outcomes enhanced due to the diagnostic assessment performed by the Fiqh subject teachers. The school management ensures that the conduct of the assessment is fraud-free, in fact, free from cheating and that students' learning outcomes improved. The observational results for two classes indicate that some students cheated because the instructor failed to remind them. Questions and answer sheets were collected by the teacher. 3) Processing and communication of the results of the diagnostic evaluation If the results of the evaluation are evaluated correctly, they will be communicated to the students and teachers and various motivational messages will be provided.